Nieformalne struktury państw Unii Europejskiej w walce z międzynarodowym terroryzmem. Bilans współpracy i wyzwania - WOJNICZ, Luiza (Przegląd Politologiczny, 2018)
The informal structures of the European Union employed in the struggle against international terrorism can be divided into those emerging inside the European Community, and those involving the states outside the EC, or third parties. The emergence of informal structures to fight terrorism resulted from the observation that the then EC did not cooperate to fight terrorism. In the 1960s and 1970s the increasing problem of terrorism stimulated efforts to look for ways to deal with it. It would have been a good solution to begin cooperation in the field of internal security on a Community scale, yet this approach stirred too many controversies and fears. Additionally, a general disinterest in political cooperation at that time made some states begin building informal structures aimed at the exchange of information on terrorist threats. It is worth emphasizing that the structures discussed in this paper (i.e. groups and clubs) are to a certain extent an element of European intelligence, as they involve intelligence agencies, structures operating within EU countries and outside, and the cooperation or synergy of intelligence provided by various mechanisms and activities. The cooperation within the framework of such structures goes beyond the EU and Europe, thus becoming more effective in fighting international, modern, globalized, non-territorial terrorism of a network character. Therefore, although the European Union has been conducting its own policy against terrorism involving all its member states, these informal structures with third parties will continue to play an important part in anti-terrorist cooperation between states that are at particular risk of terrorist activity.